PENINGKATAN PRODUKTIVITAS PADI DAN PENDAPATAN PETANI MELALUI SISTEM TANAM JAJAR LEGOWO DI LAHAN SAWAH IRIGASI - Jumakir, Jumakir; Waluyo, Waluyo; Suparwoto, Suparwoto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
The assesment aims to know performance of rice production and income farmer on rice planting system in low land irigation. The assesment was conducted in Sri Agung village, Batang Asam sub District, Tanjung Jabung Barat District on dry season 2008 on farm research wih farmer, Diperta Tanjabbar, BPP, PPL and BPTP. In the assesment farmer apply on rice planting system legowo 4:1, legowo 6:1 and tegel system (25x25 cm) with Ciherang variety planting broad 3 ha. The result showed that rice system legowo 4:1 give growth and yield better than legowo 6:1 and tegel, increasing rice production 1,12 t/ha than tegel rice planting system. Rice planting system of legowo 4:1 was found rice production 7,68 t/ha with financial profit Rp 7.618.500, legowo 6:1 give 7,15 kg/ha with financial profi Rp 6.650.000 and tegel system 6,56 t/ha with financial profit Rp 5.951.000. Rice planting system legowo 4:1 very profit economic and profit addition Rp 1.443.000/ha with R/C 2,42 so rice planting system to development feasibility more large.